Evaluation of Regulatory Immune Response in Skin Lesions of Patients Affected by Nonulcerated or Atypical Cutaneous Leishmaniasis in Honduras, Central America - Gabriela Venicia Araujo Flores; Carmen Maria Sandoval Pacheco; Thaise Yumie Tomokane; Wilfredo Sosa Ochoa; Concepción Zúniga Valeriano; Claudia Maria Castro Gomes; Carlos Eduardo Pereira Corbett; Marcia Dalastra Laurenti (Mediators of Inflammation)
In Honduras, Leishmania (L.) infantum chagasi causes both visceral leishmaniasis (LV) and nonulcerated or atypical cutaneous leishmaniasis (NUCL). NUCL is characterized by mononuclear inflammatory infiltration of the dermis, composed mainly of lymphocytes followed by macrophages with discrete parasitism. Considering that little is known about the pathogenesis of NUCL, the aim of this study was to evaluate the regulatory response in situ in skin lesions of patients affected by NUCL. Biopsies (n=20) from human cutaneous nonulcerative lesions were collected and processed by usual histological techniques. The in situ regulatory immune response was evaluated by immunohistochemistry using antihuman CD4, FoxP3, IL-10, and TGF-β antibodies. CD4+, FoxP3+, TGF-β+, and IL-10+ cells were observed in the dermis with inflammatory infiltration in all studied cases and at higher densities compared to the normal skin controls. A positive and strong correlation was observed between CD4+ and FoxP3+ cells, and a positive and moderate correlation was observed between FoxP3+ and TGF-β+ but not with IL-10+ cells. The data suggest that T regulatory FoxP3+ cells and the regulatory cytokines, especially TGF-β, play an important role in the immunopathogenesis of NUCL, modulating a cellular immune response in the skin, avoiding tissue damage, and leading to low tissue parasitic persistence.